2004
DOI: 10.1007/s10350-003-0051-4
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Cancer in the Elderly: Patients' Perception of Bowel Control After Restorative Surgery

Abstract: An elderly patient undergoing anterior resection for rectal cancer has a reasonable expectation of acceptable continence. Age alone should not be a contraindication to a restorative resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 12 publications
(12 reference statements)
0
15
0
4
Order By: Relevance
“…In this age and disease category, colonic and rectal cancer forms the second leading combined-sex cause of mortality [1]. The number of old people in our society is increasing and so is the number of elderly people with colorectal cancer [2]. The most effective treatment of colorectal cancer is an early diagnosis and radical surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…In this age and disease category, colonic and rectal cancer forms the second leading combined-sex cause of mortality [1]. The number of old people in our society is increasing and so is the number of elderly people with colorectal cancer [2]. The most effective treatment of colorectal cancer is an early diagnosis and radical surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors consider that such defecatory problems are rare and that they tend to occur in the early postoperative period, but then disappear later. [11][12][13][14] Others have indicated that most of the patients have poor clinical functional results. 15,16 Although the reason for the onset of anterior resection syndrome is unclear, it seems to be multifactorial.…”
Section: Discussionmentioning
confidence: 97%
“…In this age and disease category, colonic and rectal cancer forms the second leading combined-sex cause of mortality [1] The number of old people in our society is increasing and so is the number of elderly people with colorectal cancer [2].…”
Section: Discussionmentioning
confidence: 99%